Pregnancy post autologous stem cell transplant with BEAM conditioning for multiple sclerosis. (November 2021) - Chatterton, Sophie; Withers, Barbara; Sutton, Ian J; Milliken, Samuel T; Ma, David DF; Moore, John J; Massey, Jennifer C
Background: Given the increasing numbers of multiple sclerosis (MS) patients undergoing autologous haematopoietic stem cell transplant (AHSCT) worldwide, and with women of childbearing age overrepresented in the target population, it is increasingly important to review fertility and pregnancy outcomes following AHSCT. Objective: To evaluate the rate of pregnancy and complications post-AHSCT for MS. Method: Retrospective evaluation of the rate of pregnancy and associated complications in a cohort of patients post-AHSCT with BEAM conditioning for MS since 2010 in a tertiary referral centre. Results: In our ongoing Phase 2 trial of AHSCT for MS, 55 patients have undergone AHSCT with 30 females being of childbearing age at time of transplantation. Four pregnancies occurred following AHSCT. Two pregnancies were carried to term. No maternal or neonatal complications were reported in either case. Two pregnancies were not carried to term due to elective terminations. Both of these patients became pregnant unexpectedly 2 years following AHSCT. Of the 21 male patients, one patient has fathered three children since his AHSCT. There were no newborn complications. Conclusions: This is the first report to our knowledge on fertility outcomes in both sexes post-AHSCT for MS. Patients of both sexes should be counselled prior to treatment on infertility and contraceptive use.